2019
DOI: 10.1186/s12871-019-0755-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous noninvasive hemoglobin monitoring estimates timing for detecting anemia better than clinicians: a randomized controlled trial

Abstract: Background Hemoglobin measurement is important for transfusion decision-making. Pulse CO-Oximetry provides real-time continuous hemoglobin (SpHb) monitoring. The triage role of SpHb trends based on hemoglobin measurements was investigated. Methods In this diagnostic randomized controlled trial, 69 patients undergoing spine or cytoreductive surgery were randomly enrolled into SpHb-monitoring and standard-care groups. Diagnostic blood samples were drawn for CO-oximetry Hb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
(24 reference statements)
0
11
1
Order By: Relevance
“…When using the exclusion zones determined by measurement repeatability analysis but not excluding SpHb based on low perfusion index, SpHb concordance was 94.2%. Our findings are also better than reported in 69 patients undergoing spine or cancer surgery that employed a 1 g/dl exclusion zone [20]. A study of patients undergoing abdominal or pelvic surgery found 41 of 269 changes at any Hb had increased SpHb when ABGHb decreased, including 14 in which the decrease was more than − 1 g/dl [11].…”
Section: Discussioncontrasting
confidence: 58%
“…When using the exclusion zones determined by measurement repeatability analysis but not excluding SpHb based on low perfusion index, SpHb concordance was 94.2%. Our findings are also better than reported in 69 patients undergoing spine or cancer surgery that employed a 1 g/dl exclusion zone [20]. A study of patients undergoing abdominal or pelvic surgery found 41 of 269 changes at any Hb had increased SpHb when ABGHb decreased, including 14 in which the decrease was more than − 1 g/dl [11].…”
Section: Discussioncontrasting
confidence: 58%
“…During liver transplantation, it was also a useful trending monitor, considering that the concordance rate was 79%, but the correlation coefficient for ΔSpHb and ΔtHb was 0.79 [ 23 ]. Since Baker et al reported greater benefits of SpHb in indicating an unexpected status change, such as Hb decrease due to actual bleeding or acute hemodilution, the possible low trending ability in the presence of CO 2 insufflation should be taken into account when deciding on blood transfusion [ 3 , 10 , 21 ]. Lastly, most data points in our study existed within the central exclusion zone, which means that Hb did not change appreciably, which may be because blood sampling during laparoscopic gastrectomy may be primarily due to the assessment of the acid-base status or electrolyte rather than a clinical suspicion of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 For a timely blood transfusion, the trending capability of SpHb is important, and it more accurately estimates the appropriate timing for invasive Hb measurements than do clinicians. 22 , 25 - 27 However, SpHb monitoring is still controversial for postoperative management. It was reported to be unsuitable to maintain the Hb level >8 g/dL, particularly in those with lower Hb levels in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“… 19 At this time, SpHb might be used as a good indicator to determine when laboratory measurement of Hb is essential to make the final decision on blood transfusion. 26 Further studies are needed in various postoperative situations in the future.…”
Section: Discussionmentioning
confidence: 99%